Effects of Blending Semolina with Egg Powder on Physico- Chemical and Sensory Quality of Macaroni - Anbesse Girma; Geremew Bultosa; Solomon Abera (Journal of Food Science and Nutrition Therapy - Peertechz Publications, 2019)
A study was conducted to improve the nutritional status of macaroni product by adding egg powder to semolina flour. The effects of five proportions of egg powder (20%, 25%, 30%, 35% and 40%) were investigated. The result showed that with increase in egg proportion, increase in protein, fat, ash and a reduction in fiber and carbohydrate were observed. Improvement in Fe, Ca and Zn were also observed. Farinograph dough rheology evaluation indicated a drop in water absorption, stability time, time to dough viscosity break and tolerance index. On the other hand, increase in dough development time was noticed. Increase in the egg powder proportion resulted in the reduction of optimum cooking time and hardness. At the same time the water uptake capacity and cooking loss were increased. Addition of egg powder improved the color acceptability in general. However the various proportions didn't show significant difference in color and homogeneity. Sensory evaluation score of macaroni stickiness increased and that of springiness decreased with increase in egg proportion. Overall acceptability decreased with increased in egg proportion. From all trials macaroni with 20, 25 and 30% egg powder were acceptable in many sensory quality attributes and product properties. Macaroni with 30% egg powder, in addition to those qualities, has much better nutrient chemical composition and functional properties than the others.